تقويم أداء المصرف التجاري السوري من منظور بطاقة الأداء المتوازن (دراسة ميدانية على فروع المصرف التجاري السوري في مدينة اللاذقية) - زاهر, بسام; بواط, غادة; اسبر, لمى (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يقدم البحث دراسة للواقع الحالي للمصرف التجاري السوري وآلية تنفيذ عملياته والأهداف التي يتوخى تحقيقها، من خلال بطاقة الأداء المتوازن كما يقدم شرحاً نظرياً لمفهوم بطاقة الأداء المتوازن من حيث اعتماده على أربعة جوانب هي ( الجانب المالي –العملاء-العمليات الداخلية –التعلم والنمو). توصلت الدراسة إلى النتائج التالية: أن المصرف نجح في تحقيق أهدافه في الربحية والأمان المصرفي، إلا أنه لم ينجح في إرضاء العملاء، ولم ينجح في تحقيق هدف تحسين العمليات الداخلية، كما أنه لم ينجح في تحقيق التطوير والتعلم والابداع في الأنظمة والاجراءات والموظفين. وقدم البحث مجموعة من التوصيات منها: تبني مفهوم بطاقة الأداء المتوازن في قياس الأداء وتعميق مفهومه في ثقافة المصرف، ضرورة الاهتمام بالعملاء ومقترحاتهم وتحقيق رضاهم، ضرورة الاهتمام بتحسين جودة العمليات المصرفية وتقديم الخدمات بلا أخطاء وبأسرع وقت ممكن، وتركيز الاهتمام بالموارد البشرية في المصرف وتمكينها في العمل لزيادة درجة رضا الموظفين وتحسين إنتاجيتهم. The research presents a study and evaluation of the current situation of the Commercial Bank of Syria and the mechanism for implementation of its operations and goals to be achieved, through Balanced Scorecard also provides an explanation of the concept of Balanced Scorecard in terms of its dependence on four aspects are (financial - customers - internal processes- learning and growth). The study reached the following conclusions: that the bank has succeeded in achieving its objectives in profitability and security of banking, but it did not succeed in satisfying customers, in achieving the goal of improving internal operations, and it did not succeed in achieving learning and innovation in procedures and staff . The research was presented a set of recommendations including: Adoption of the concept of Balanced Scorecard in performance measurement and deepen his understanding of the culture of the bank, the need to focus attention to customers and their proposals and to achieve satisfaction, the need for attention to improving the quality of banking operations and provide services without errors as soon as possible, and to focus attention to human resources at the bank and enable work to increase the degree of employee satisfaction and improve productivity.